Economic and Organizational Aspects of Solar Energy Utilization Through Technology (Journal of Universal Excellence, 2026)
Research Question (RQ): How can households and businesses optimally harness solar energy in hybrid systems with or without energy storage, considering the new five-tariff system for electricity billing in Slovenia, aiming to reduce costs and improve energy efficiency?.Purpose: We aim to demonstrate the aspect of optimal energy utilization in households leveraging solar energy, taking into account the new time block and billing system.Method: We conduct a theoretical examination of relevant literature and illustrate the calculated electric energy obtained entirely from solar sources, considering the time block and disregarding it.Results: The results indicate the need for thoughtful adjustments in household consumption to avoid higher tariff payments. Monthly costs of agreed power are 31.73% lower for consumers utilizing solar energy with an integrated energy storage system and smart technology, compared to those without it. The analysis reveals a 26.94% higher annual cost for the first consumer under the new billing model, emphasizing the benefits of technological adaptation and energy planning. Consumers without energy storage face a transmission cost of €125.42 for 10 MWh, while those with an optimal storage system can achieve savings, halving the energy flow through the network and, consequently, reducing costs. The study finds that the transmission fee will represent a significantly smaller portion of the consumer's financial burden. The agreed power plays a more substantial role in the final transmission fee and, consequently, consumer costs.Organization: The research provides valuable insights for managers and organizations concerning the optimal use of solar energy in hybrid systems. The integration of smart technologies and energy storage allows organizations to reduce costs and manage time blocks more efficiently, contributing to increased energy efficiency.Society: The impact of the research on society lies in promoting sustainable practices and reducing network load. The adoption of solar technologies and smart energy management encourages responsible resource use, contributing to social responsibility and sustainable development.Originality: The contribution is original in analyzing the impact of hybrid systems on costs and efficiency, particularly considering new time blocks for electricity billing. The emphasis on smart technology, energy storage, and their impact on costs and the network brings new aspects to understanding the optimal use of solar energy.Limitations / further research:  Limitations of the study include the specificity of the considered tariff scheme for the Slovenian region and the generalizability of results across diverse conditions. Further research could expand the analysis to multiple regions, include other energy sources, and consider different organizational sizes.
Keywords: solar energy; cost analysis; technology; network cost; energy storage; hybrid systems; smart energy management; five-tariff system